The potential use of giant reed from Portugal as a thermal insulation material - Raphaele Malheiro; Aurora Morilla; Adriana Ansolin; Jorge Fernandes; Sandra Silva; Ricardo Mateus (Acta Polytechnica CTU Proceedings)
The construction sector plays an important role in climate change. Thus, there is a pressing need to construct buildings that reduce heat losses, use natural and local materials, exploit renewable sources and ensure high comfort levels with a minimum environmental impact. Reed, considered carbon-neutral and a carbon dioxide sink material, has been used for centuries for diverse uses. Its properties and high availability made it a popular building material, as seen in Portuguese vernacular architecture. Knowing the properties of the reed is a crucial step to ensure successful heritage conservation, optimising these materials, and developing innovative solutions. This paper studies the potential of using giant reed from different Portuguese regions as a thermal insulation material. Giant reed board prototypes (15 x 15 x 5 cm, about 235 kg/m3) were built. Their thermal performance was tested in a hotbox, according to ASTM C1363‑19. The results show that the giant reed harvested on the northern coast of Portugal has better thermal performance than reeds from other regions. However, regardless of the region of the country where the giant reed was harvested, it has a satisfactory thermal resistance (Re ≥ 0.30 (m2.ºC)/W), allowing its use as a thermal insulation material in the buildings.